Integrated Energy Policy - Planning Commission (Planning Commission Government of India, 2008)
India's Integrated Energy Policy (December 2008) provides a comprehensive strategy to address the nation’s growing energy demand, supply challenges, and environmental concerns while supporting inclusive economic growth. Recognizing that nearly 600 million people lack electricity and 700 million rely on biomass for cooking, the policy emphasizes improving energy access and affordability, particularly for vulnerable populations. Key goals include achieving a sustained economic growth rate of 9% by 2031-32, necessitating a four- to five-fold increase in primary energy demand and a six-fold expansion in power generation capacity. The policy advocates the strategic utilization of diverse domestic energy resources — including coal, hydro, oil, gas, renewables, and nuclear energy — coupled with enhanced energy efficiency and reductions in greenhouse gas emissions. Implementation relies on coordinated actions across central and state agencies, transparent pricing mechanisms, subsidy reforms, and private sector participation to strengthen energy infrastructure. Renewable energy and thorium-based nuclear power are highlighted as critical avenues for sustainable, low-carbon growth. Overall, the policy lays a roadmap for ensuring energy security, environmental sustainability, and broad-based access to affordable energy, thereby supporting India’s inclusive development objectives.
Government of India Planning Commission December 2008
Keywords: Integrated Energy Policy; Energy Security; Renewable Energy; Coal Supply; Nuclear Energy; Power Generation; Energy Efficiency; Environmental Sustainability; Energy Access; Pricing Reforms; Infrastructure Development; Inclusive Growth